Species profiles life histories and environmental requirements of coastal fishes and invertebrates--Common lettleneck clam - Shaw, William N. (Washington, D.C. U.S. Department of the Interior, 1986)
U.S. Fish Wildl. Serv. Biol. Rep. 82(11.46)
Keywords: Invertebrates; Fishes; History; Common littleneck clam--Pacific Southwest